Evaluation of Cariogenic Bacteria - Nishikawara, Fusao; Nomura, Yoshiaki; Imai, Susumu; Senda, Akira; Hanada, Nobuhiro (European Journal of Dentistry, 2007)
Objectives : The evaluation of Mutans streptococci (MS) is one of the index for caries risk. DentocultTM and CRTTM are commercial kits to detect and evaluate MS, conveniently. However, the evaluation of MS has also been carried out simply using an instruction manual. But the instruction manual is not easy to use for evaluation of MS. The aim of this study was to examine the utility of modified Mitis-Salivalius Bacitracin (MSB) agar medium compared with MSB agar medium and commercial kits, and to establish a convenient kit (mMSB-kit) using modified MSB agar.Methods : The MS in stimulated saliva from 27 subjects were detected by MSB, modified MSB agar medium and commercial kits. Laboratory and clinically isolated strains of MS were similarly evaluated. The ratios of MS in detected bacteria were compared by ELISA.Results : The scores using an mMSB-kit on the basis of modified MSB agar medium were tabulated. Saliva samples showed different levels of MS between culture methods and the commercial kit. Some samples which were full of MS were not detected by the commercial kit. The detection of MS by modified MSB agar medium and mMSB-kit were significantly higher when compared with MSB agar medium, CRTTM, (P< .01) and Dentocult SMTM (P<.05).Conclusion : The sensitivity for detection of MS is higher for modified MSB agar medium when compared with MSB agar medium. The mMSB-kit can be used simply, and can be an important contributor for the evaluation of MS as a caries risk factor. (Eur J Dent 2007;1:31-39)
Keywords: Commercial kits; Culture methods; Streptococci mutans; Streptococcus sobrinus